Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.str.2017.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Water Molecules in Proton Translocation by the Membrane-Bound Transhydrogenase

Abstract: Summary The nicotinamide nucleotide transhydrogenase (TH) is an integral membrane enzyme that uses the proton motive force to drive hydride transfer from NADH to NADP+ in bacteria and eukaryotes. Here we solved a 2.2 Å crystal structure of the TH transmembrane domain (Thermus thermophilus) at pH 6.5. This structure exhibits conformational changes of helix positions from a previous structure solved at pH 8.5, and reveals internal water molecules interacting with residues implicated in proton translocation. Toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…During MD simulations, a transient water wire is formed connecting His42 α2 and Glu221 β through the hydrophobic barrier, and the presence of the water wire coincides with a conformational change of Thr214 β side chain located slightly below His42 α2 . Mutation of Thr214 β to Ala causes >90% loss of channel-coupled enzymatic activity, biochemically supporting the proposed role of Thr214 β in proton translocation (Padayatti et al, 2017 ).…”
Section: Structures Of Transmembrane Domain IIsupporting
confidence: 61%
See 3 more Smart Citations
“…During MD simulations, a transient water wire is formed connecting His42 α2 and Glu221 β through the hydrophobic barrier, and the presence of the water wire coincides with a conformational change of Thr214 β side chain located slightly below His42 α2 . Mutation of Thr214 β to Ala causes >90% loss of channel-coupled enzymatic activity, biochemically supporting the proposed role of Thr214 β in proton translocation (Padayatti et al, 2017 ).…”
Section: Structures Of Transmembrane Domain IIsupporting
confidence: 61%
“…Structural determination of the transmembrane domain of TH has recently been achieved by the use of lipidic cubic phase (LCP) crystallization (Leung et al, 2015 ; Padayatti et al, 2017 ). The LCP is a viscous bilayer matrix that is thought to better stabilize membrane proteins than detergents and more frequently results in a tighter and layered crystal packing (Caffrey and Cherezov, 2009 ).…”
Section: Structures Of Transmembrane Domain IImentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to proteins, not only does it provide the necessary energetic conditions required for faithful folding [2][3][4] but also mediates enzymatic activity and facilitates substrate specificity [5,6]. In addition, there are instances of specific water molecules that fulfill critical biological roles contributing to a protein's conformational stability [7], enabling proton translocation in the membrane-bound transhydrogenase [8], mediating an antigenantibody association [9], or manifestly contributing to ligand binding [10][11][12]. Recently, we demonstrated that considering the particularly strongly interacting water molecules when designing drugs allows the identification of ligands that are specific to a particular protein ortholog [13].Although the surface of most proteins is generally hydrophilic, interactions between water molecules and atoms comprising the protein are transient.…”
mentioning
confidence: 99%